1995
DOI: 10.1901/jeab.1995.64-47
|View full text |Cite
|
Sign up to set email alerts
|

Food‐deprivation Effects on Punished Schedule‐induced Drinking in Rats

Abstract: Food-deprived rats (at 80% of their free-feeding weights) were exposed to a fixed-time 60-s schedule of food-pellet presentation and developed schedule-induced drinking. Lick-dependent signaled delays (10 s) to food presentation led to decreased drinking, which recovered when the signaled delays were discontinued. A major effect of this punishment contingency was to increase the proportion of interpellet intervals without any licks. The drinking of yoked control rats, which received food at the same times as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
4
11
1
1
Order By: Relevance
“…Even though the behavior of drinking was not completely suppressed, the establishment of this contingency led to lower rates of drinking regardless of whether or not the delays were signaled. These results were later replicated (Lamas & Pellón, 1995;Pellón & Castilla, 2000) and have been shown to be very similar to the results normally found when a well-established operant behavior is punished. It has also been seen that resistance to punishment is related to the deprivation levels in operant behavior, just as it is in schedule-induced drinking (Lamas & Pellón, 1995).…”
Section: Are Adjuncts Operants?supporting
confidence: 72%
See 2 more Smart Citations
“…Even though the behavior of drinking was not completely suppressed, the establishment of this contingency led to lower rates of drinking regardless of whether or not the delays were signaled. These results were later replicated (Lamas & Pellón, 1995;Pellón & Castilla, 2000) and have been shown to be very similar to the results normally found when a well-established operant behavior is punished. It has also been seen that resistance to punishment is related to the deprivation levels in operant behavior, just as it is in schedule-induced drinking (Lamas & Pellón, 1995).…”
Section: Are Adjuncts Operants?supporting
confidence: 72%
“…As operants are defined by their consequences, a way to test this hypothesis would be to establish a contingency between the behavior of licking a waterspout and the delivery of food pellets. This contingency has previously been employed in several experiments in which the behavior of drinking was punished by a delay in the delivery of food (Lamas & Pellón, 1995;Pellón & Blackman, 1987;Pellón & Castilla, 2000), thus lengthening the interfood interval. Those studies concluded that adjunctive drinking was subject to punishment but left unanswered the question of whether it was developed by a contingent food schedule (see Patterson & Boakes, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, food restriction level obviously affects choice in delayed-reinforcement paradigms, with more severe restriction having more marked motivation-enhancing effects (Bradshaw et al, 1983;Ho et al, 1999; see also among others: Leander, 1973;Takahashi and Singer, 1980;Papasava et al, 1986;Lamas and Pellón, 1995;Haberny et al, 2004). Each animal was then placed daily in a computer-controlled operant chamber (Coulbourn Instruments, Allentown, PA, USA), provided with two nose-poking holes, a chamber light, a feeder device, a magazine where pellets (45 mg, BioServ, Frenchtown, NJ, USA) were dropped, and a magazine light.…”
Section: Behavioral Impulsivity Taskmentioning
confidence: 99%
“…Dentre os estudos com polidipsia, muito tem-se investigado sobre o efeito da manipulação de drogas ou lesões neuroquímicas com vistas a entender o controle central desse comportamento, como por exemplo, os estudos de Bowers, Halberda, Mullen e May (1997); Cirulli, Van Oers, De Kloet e Levine (1994); Didriksen, Olsen, e Christensen (1993); Flores e Pellon (1997); Lu, Tseng, Wan, Yin e Tung (1992); Mittleman, Blaha, e Phillips (1992). Os estudos sem droga manipulam variáveis diversas, porém a mais consistentemente investigada tem sido a conseqüênciação da polidipsia em desenvolvimento ou já instalada (Allan & Matthews, 1992;Lamas & Pellon, 1995a, 1995bLamas & Pelon, 1997). Esses estudos têm mostrado que o comportamento induzido é sensível ao controle operante.…”
Section: Comentários Finaisunclassified